THE ROLE OF THE VILLAGE AND LOCAL COMMUNITY IN PRESERVING NATURE IN THE ULU PETANU WATERFALL AREA, GIANYAR REGENCY, BALI - Indra Pranata Darma, I Gusti Ketut; I Nyoman Piartha (International Journal of Social Studies, 2025)
Ulu Petanu Waterfall has become one of the emerging natural tourist attractions in Gianyar Regency. The pristine nature of this waterfall serves as a unique appeal compared to similar locations within the Gianyar area. Based on the Tourism Area Life Cycle (TALC), this attraction is currently in the second stage, namely the development phase. At this stage, several challenges have begun to emerge, including the development of supporting facilities around the site, road access, and potential conflicts among local communities regarding the tourism attraction’s development. This study employs a qualitative descriptive method through in-depth interviews with the attraction’s managers, local residents, and nearby vendors. The main focus of this research is to identify the development boundaries and sustainable development plans, particularly the needs of the Kedisan Village community in Gianyar Regency, Bali. The research findings indicate that the village management, under the supervision of Kedisan Village, still demonstrates enthusiasm for independent management in line with the destination life cycle. The self-managed development of the tourist attraction continues to progress well, as the community affected by the waterfall’s presence is still able to cooperate effectively, supported by the influence of local community leaders who play a significant role in Kedisan Village’s social life. However, in the future, attention should also be given to the continuity of these community leaders’ roles, especially since the advancement of information technology will lead the younger generation to become more open and influenced by external factors.